Digital Learning Workshop for Primary Physical Education Teachers During Covid-19 Pandemic - Anggi Setia Lengkana; Ayi Suherman; Rizal Ahmad fauzi; Tatang Muhtar; Dinar Dinangsit (Jurnal Humanities Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service activity is to introduce several forms of digital-based physical education learning in the COVID-19 pandemic era for PJOK teachers in Sumedang Regency. After analyzing the situation, several problems were identified as follows: (1) There are still PJOK teachers who have not delivered physical education materials during this COVID-19 pandemic with digital-based learning media, (2) There is still a lack of knowledge of PJOK teachers about how to form digital learning media for students. children, (3) There are still PJOK teachers who tend to focus more on giving assignments through the Whatsapp group instead of explaining the material using digital learning media. Therefore, this training is a solution for PJOK teachers to try to open scientific horizons regarding digital learning in physical education.